2022
DOI: 10.1172/jci153357
|View full text |Cite
|
Sign up to set email alerts
|

β3-Adrenergic receptor downregulation leads to adipocyte catecholamine resistance in obesity

Abstract: The dysregulation of energy homeostasis in obesity involves multi-hormone resistance. Although leptin and insulin resistance have been well characterized, catecholamine resistance remains largely unexplored. Murine b3-adrenergic receptor expression in adipocytes is orders of magnitude higher compared to other isoforms.While resistant to classical desensitization pathways, its mRNA (Adrb3) and protein expression are dramatically downregulated after ligand exposure (homologous desensitization). b3-adrenergic rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 86 publications
7
64
0
Order By: Relevance
“…However, ADRβ3 and GIPR expression is markedly down-regulated in adipose tissue of obese human subjects in this study. This is consistent with other studies that have reported downregulation of these receptors in the adipose tissue of high fat-fed mice as well in human obese subjects (37)(38). Therefore, the approach to using agonists of these receptors to mitigate obesity and related disorders is unlikely to work.…”
Section: Discussionsupporting
confidence: 89%
“…However, ADRβ3 and GIPR expression is markedly down-regulated in adipose tissue of obese human subjects in this study. This is consistent with other studies that have reported downregulation of these receptors in the adipose tissue of high fat-fed mice as well in human obese subjects (37)(38). Therefore, the approach to using agonists of these receptors to mitigate obesity and related disorders is unlikely to work.…”
Section: Discussionsupporting
confidence: 89%
“…Using time-lapse total internal reflection fluorescence (TIRF) microscopy of GLUT4-GFP in primary adipocytes, GLUT4 near the plasma membrane was found either localised within relatively stationary clusters or in mobile structures thought to be GSCs adjacent to the plasma membrane 18 . High resolution imaging of surface-exposed GLUT4 inserted into the plasma membrane using antibodies directed against the exofacial HA epitope confirmed that GLUT4 distribution within the plasma membrane is inhomogeneous, being identified both in clustered domains and as a diffuse staining 18 , 19 . The authors identified two distinct modes of GLUT4-vesicle exocytosis.…”
Section: Introductionmentioning
confidence: 85%
“…β3-adrenergic receptor (β3-AR) is a seventransmembrane domain G-protein coupled receptor and its stimulation increases the production of cAMP [21], [24], [25]. β3-AR is expressed in many tissues including the reproductive system, urinary system, CNS, and adipose tissue [26], [27].…”
Section: Discussionmentioning
confidence: 99%